Optimizing the conditions for devulcanization of rubber waste by thiobacillus ferroxidans / Ainie Asyikin Ahmad ...[et al.] - Ahmad, Ainie Asyikin; Yusof, Faridah; Abdul Rahim, Ahmad Nazree; Shahari@Ansari, Khater Sharifa; Ahmad Barkat, Anumsima (2008)
Vulcanized rubber is chemically stable. It is difficult to combine it into new material because bonding between the new material and the vulcanized rubber is weak. Present devulcanization process is costly, hence only a small percentage of waste rubber can be recycles, thus a need for a cost effective devulcanization process would permit a substantially greater portion of waste vulcanized rubber to be recycled. Enzymatic devulcanization has been successfully attempted by using bacteria Thiobacillus ferroxidans. This bacteria releases tetrathionate hydrolase that helps to alter the sulphur chains that crosslinked rubber molecules in vulcanized rubber products, after which the rubber surface is now ready to accept virgin rubber during recycling process. Factorial design was applied to determine the optimal physical condition and medium composition for minimum doubling time and maximum protein secretion and accumulation by Thiobacillus ferroxidans. Six independent variables, temperature, initial pH, KH2P04, (NH4)2S04, MgS04 and CaCl2 in the growth medium were tested. KH2P04, pH, (NH4)2S04, MgSO4. was found to promote positive correlation with the minimum doubling time and maximum protein secretion and accumulation. The optimal composition of the growth medium to achieve the minimum doubling time and maximum protein secretion and accumulation was determined as follows (g/l): KH2PO4 = 5, (NH4)2SO4. = 7.5, MgS04 = 0.25, CaCl2= 0.25 at initial pH of 4 and 25°C. The corresponding doubling time and protein concentration were 25.92 hours and 67.5µg/ml, which are about 2.0 fold decrease and 2. 88-fold increase, respectively, compared with those using the conventional T ferroxidans growth medium.